연간 부분부하 운전특성을 고려한 모듈러 데이터센터의 냉각시스템 효율 분석 - 정용호(Yong-Ho Jung) (KIEAE Journal, 2019)
Purpose: Edge computing is indispensable as the demand for fast communication speeds such as autonomous vehicles increases. Edge computing services, which are distributed near processing units, require small and distributed data centers. Currently, in the case of distributed modular data centers, adaptation to domestic weather conditions has arisen by introducing foreign technology directly. In this study, the annual efficiency due to the partial load operation of the cooling system was identified through the energy consumption prediction when the container-type basic module was applied in each region in Korea. Method: E-quest was used to forecast annual energy consumption. Considering the partial load to determine the efficiency of the annual cooling system, the SEER was calculated based on the total input energy and the required energy and the energy consumption efficiency of each region was compared and analyzed. Result: Container-type modular data centers account for 9.2 ~ 21.8% depending on the location of the external load impact. The distribution of SEER was found to be high at 14.04 in the Central 2 region but low at 12.09 in the Jeju region where the outside air temperature was high. In the case of installing cooling facilities of the same capacity, the energy consumption efficiency is different for each region. Therefore, it is necessary to select the capacity considering the local weather conditions when selecting the cooling facilities. KCI Citation Count: 0